Atomically dispersed Pd electrocatalyst for efficient aqueous phase dechlorination reaction - Mao, Zhechuan (2022)
High atom utilization is important for practical application of Pd catalysts in dechlorination of chlorinated organic pollutants (COPs). Herein, we report atomically dispersed Pd (coordinated with 2 pyridinic N) anchored on N-doped carbon (A-Pd-NC) as an efficient catalyst toward electrochemical dechlorination of COPs in aqueous solution. Constant current electrolysis showed that the A-Pd-NC catalyst possessed a much higher dechlorination activity (DA, 98.9 mmol•g−1•h−1) than commercial Pd/C (2.4 mmol•g−1•h−1). Using A-Pd-NC as an effective electrocatalyst, near 100% product selectivity of 4-chlorophenol to phenol could be achieved at pH = 3. Constant potential electrolysis, cyclic voltammetry (CV), electron spin resonance (ESR), X-ray photoelectron spectroscopy (XPS) and density functional theory (DFT) calculation results suggested that the dechlorination stability of A-Pd-NC was dependent on the potential applied on the catalyst and the dechlorination reaction followed the hydrodechlorination mechanism with electrochemically adsorbed H as the reductant.